JNK Signaling Pathway Mediates Acetaminophen-Induced Hepatotoxicity Accompanied by Changes of Glutathione S-Transferase A1 Content and Expression - Shi, Chenxi; Hao, Beili; Yang, Yang; Muhammad, Ishfaq; Zhang, Yuanyuan; Chang, Yicong; Li, Ying; Li, Changwen; Li, Rui; Liu, Fangping (Frontiers in Pharmacology, 2019)
Acetaminophen is an analgesic-antipyretic drug and widely used in clinics. Its overdose may cause serious liver damage. Here, we examined the mechanistic role of JNK signaling pathway in liver injury induced by different doses of acetaminophen. Male mice were treated with acetaminophen (150 and 175 mg·kg-1) and meanwhile JNK inhibitor SP600125 was used to interfere acetaminophen-induced liver damage. The results showed that JNK signaling pathway was activated by acetaminophen in a dose-dependent manner. JNK inhibitor decreased JNK and c-Jun activation significantly (P < 0.01) at 175 mg·kg-1 acetaminophen dose, and phosphorylation levels of upstream proteins of JNK were also decreased markedly (P < 0.05). In addition, serum aminotransferases activities and hepatic oxidative stress increased in a dose-dependent manner with acetaminophen-treatment, but the levels of aminotransferases and oxidative stress decreased in mice treated with JNK inhibitor which implied that JNK inhibition ameliorated APAP-induced liver damage. It was observed that apoptosis was increased in APAP-induced liver injury, and SP600125 can attenuate apoptosis through the inhibition of JNK phosphorylation. Meanwhile, glutathione S-transferases A1 (GSTA1) content in serum was enhanced, while GSTA1 content and expression in liver reduced significantly with administration of acetaminophen (150 and 175 mg·kg-1). After inhibiting JNK, GSTA1 content in serum decreased significantly (P < 0.01), meanwhile, GSTA1 content and expression in liver enhanced. These findings suggested that JNK signaling pathway mediated acetaminophen-induced hepatic injury, which was accompanied by varying GSTA1 content and expression in liver and serum.